(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2018)
The paper considers the problem of compound bending of non-uniform round flexible plate subjected to lateral load under temperature changes through the thickness of the plate with the influence of tension on bending. The problem is reduced to the study of an unrelated system of differential equations, analytical solution of which has not been possible using existing mathematical apparatus. The paper managed to decompose the related system of equations into two unrelated equations and to find a solution using the method of partial discretization of differential equations. Results are represented as formulae and graphs